PENETAPAN KADAR FENOLIK TOTAL EKSTRAK METANOL KELOPAK BUNGA ROSELLA MERAH (Hibiscus sabdariffa Linn) DENGAN VARIASI TEMPAT TUMBUH SECARA SPEKTROFOTOMETRI - Riza Alfian; Hari Susanti (Pharmaciana, 2012)
The purpose of this research is to determine the total phenolic content of Hibiscussabdariffa calyx in variations of growing area. Red Rosell calyxs were collected fromGlagah, Kediri, and Samigaluh. Phenolic compounds of Hibiscus sabdariffa calyx wereextracted using maceration method with methanol. Total phenolics content weredetermined using visible spectrophotometry method with Folin Ciocalteau reagent. Theprinciple of this method is the formation of blue complex compound fromphospomolybdate-phosphotungstate reduced by phenolic compound in the basiccondition, which can be measured by spectrophotometry. Galic acid was used ascomperator in this research. Total phenolic content in red calyx Glagah, Kediri andSamigaluh were respectively 1.40 g GAE/100 g extract, SD 0.06 (n=12), 1.41 gGAE/100 g extract, SD 0.07 (n=12) dan 2.12 g GAE/100 g extract, SD 0.05 (n=15).Based on this results it could be concluded that growing area affected total phenoliccontent in the methanol extract of red calyx Rosell.